Impact of procurement professionalization on the efficiency of public procurement - Riyadi Wibowo (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
Each year the central and regional governments spend up to 1,000 trillion rupiahs for procurement of goods and services. In the past, government procurement of goods and services was exposed to leakage and corruption. If the leak is 30 percents, it means that the lost cost of 250 trillion rupiahs. Procurement professionals are key to addressing this problem. By enhancing procurement skills to employees implementing Procurement Services Unit (PSU), Procurement professionals aim to improve the efficiency of procurement of government goods and services, ensure timely availability of goods and services, and provide public services as planned. Through budget efficiency and savings, more and more quality goods and services will be earned so that they have a positive impact on economic growth. The Six Sigma approach with DMAIC stage series (define, measure, analyze, improve, control) is used as a reference to measure and analyze the effect of acquiring skills improvements. Observation 43 Pilot PSUs earned a budget efficiency of 14% or equivalent to 58 trillion rupiahs accumulated during the 2012-2017 period.